Quality of life measurement in atopic dermatitis. Position paper of the European Academy of Dermatology and Venereology (EADV) Task Force on quality of life. (17th January 2017) - Chernyshov, P.V.; Tomas‐Aragones, L.; Manolache, L.; Marron, S.E.; Salek, M.S.; Poot, F.; Oranje, A.P.; Finlay, A.Y.; ,
Abstract: There is a need for researchers to have easy reference to the wide spectrum of different types of quality of life (QoL) instruments that can be used in atopic dermatitis (AD). Previous reviews on QoL in AD do not cover the full spectrum of QoL measures used in studies on AD. This study, on behalf of the European Academy of Dermatology and Venereology (EADV) Task Force on QoL, contains information on instruments available for health‐related QoL and family QoL assessment in AD including information on validation, experience of QoL assessment in AD for different purposes, peculiarities of QoL assessment in different age groups, expert analysis of available instruments including data on limitations of their use and recommendations of the Task Force.